Quasi-static analysis of scattering from a radially uniaxial sphere with dispersive coating in chiral medium. Issue 16 (1st November 2016) - Qayyum, Adil; Abbas, Farhat; Naqvi, Qaisar A.
Abstract: The presented manuscript addresses the quasi-static analysis of a dispersive coated radially uniaxial (RU) sphere placed in an unbounded chiral medium. Dispersion has been included through Lorentz–Drude model. RU medium is defined as having dyadic permittivity and/ or permeability. In this manuscript only permittivity of the sphere has been taken to be dyadic. Expressions for the internal fields of sphere have been calculated and discussed. The scattered fields response in terms of polarizability have been studied for different coated materials. Results of the given geometry compared with the results of special cases, dielectric sphere placed in free space and layered dielectric spheres placed in chiral medium for validation of results.